2022
DOI: 10.2147/ijwh.s365943
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Regulates the Expression and Function of lncRNA-H19 in Ectopic Endometrium

Abstract: Background: Long noncoding RNAs (lncRNAs) are involved in the pathogenesis of endometriosis and can be regulated by estrogen. This study aimed to investigate the role of estrogen in regulating the expression and function of lncRNA-H19 in endometriosis. Methods: Endometrial stromal cells (ESCs) were isolated from ectopic, eutopic endometrium with endometriosis and control endometrium without endometriosis, and lncRNA-H19 expression was detected using real-time polymerase chain reaction (RT-PCR). Ectopic endomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Banz et al, using the microarray technique, showed differences in gene expression in endometrial carcinoma tissue and endometroid carcinoma arising in the scopeof endometriosis [50]. H19 is involved in the pathogenesis of endometriosis by modulating the proliferation and invasion of ectopic endometrial cells [18]. In a study by Liu et al lncRNA H19 showed the greatest upregulation in the ectopic and eutopic endometrium [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Banz et al, using the microarray technique, showed differences in gene expression in endometrial carcinoma tissue and endometroid carcinoma arising in the scopeof endometriosis [50]. H19 is involved in the pathogenesis of endometriosis by modulating the proliferation and invasion of ectopic endometrial cells [18]. In a study by Liu et al lncRNA H19 showed the greatest upregulation in the ectopic and eutopic endometrium [51].…”
Section: Discussionmentioning
confidence: 99%
“…17β-estradiol is known to play a role in regulating H19 expression and function in endometriosis patients. 17β-estradiol is therefore involved in the development of endometriosis by regulating H19 [18]. H19 regulates endometrial tissue proliferation by altering IGF signaling in endometriosis [19].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that 17β-estradiol plays a role in regulating the expression pattern and function of H19 in patients with endometriosis. Based on these findings, it can be concluded that 17β-estradiol is involved in the development of endometriosis through the regulation of H19 [ 98 ]. According to a study by Sedigheh et al, the expression level of H19 was found to be significantly decreased in both ectopic and eutopic endometrial tissues compared to control tissues.…”
Section: Exploring the Significance Of Lncrna H19 In Gynecologic Canc...mentioning
confidence: 99%
“…Studies have shown that H19 expression is noticeably higher in the ectopic endometrium of patients with endometriosis than in the normal endometrium [ 31 ]. Alterations in the H19/miR-216a-5p/actin alpha 2 (ACTA2) pathway may be involved in H19-mediated invasion and migration of ectopic ESCs, which could be an underlying cause of fibrogenesis or fibrosis in patients with endometriosis [ 32 ].…”
Section: H19 and Endometriosismentioning
confidence: 99%